Molecular indicators of denervation in aging human skeletal muscle. Issue 4 (29th July 2019) - Soendenbroe, Casper; Heisterberg, Mette F.; Schjerling, Peter; Karlsen, Anders; Kjaer, Michael; Andersen, Jesper L.; Mackey, Abigail L.
Abstract: Introduction: Muscle fiber denervation increases with age, yet studies at the tissue level are sparse due to the challenging nature of establishing the relative role of regeneration and denervation. Methods: Muscle biopsies were obtained from the vastus lateralis of 70 healthy men (aged 72 ± 6 years; range, 65–94). Messenger RNA (mRNA) levels of acetylcholine receptors (AchR) were measured, and sections were stained for embryonic myosin, neonatal myosin (MHCn ), and neural cell adhesion molecule (NCAM). Results: Embryonic myosin + fibers were rare, while MHCn + and NCAM + fibers were observed in all samples. Age (range, 65–94 years) was negatively associated with AchRγ mRNA. Discussion: Muscle from healthy older individuals expressed developmental myosins to varying degrees but more than has been previously reported for young individuals. Along with the AchR correlations, we propose that these findings support the presence of neuromuscular junction destabilization, denervation, and reinnervation in aging human skeletal muscle.